2006
DOI: 10.1007/s11430-006-8113-9
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary study on assessment of nutrient transport in the Taihu Basin based on SWAT modeling

Abstract: With the Taihu Basin as a study area, using the spatially distributed and mechanism-based SWAT model, preliminary simulations of nutrient transport in the Taihu Basin during the period of 1995~2002 has been carried out. The topography, soil, meteorology and land use with industrial point pollution discharge, the loss of agricultural fertilizers, urban sewerage, and livestock drainages were all considered in the boundary conditions of the simulations. The model was calibrated and validated against water quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 13 publications
2
16
1
Order By: Relevance
“…The external N and P (including point and non-point sources) supplied to Taihu is dominated by riverine discharge. On the basis of the spatially distributed and mechanistic SWAT Model, Lai et al(2006) suggested that sewage released to the rivers was the most important nutrient source, and the industrial point sources were the second highest contribution, each contributing 31% and 30% to TN and 47% and 16% to TP, respectively. Agricultural fertilizer application and livestock were also important nutrient sources, which contributed 15% and 10% to TN, and 14% and 11% to TP, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The external N and P (including point and non-point sources) supplied to Taihu is dominated by riverine discharge. On the basis of the spatially distributed and mechanistic SWAT Model, Lai et al(2006) suggested that sewage released to the rivers was the most important nutrient source, and the industrial point sources were the second highest contribution, each contributing 31% and 30% to TN and 47% and 16% to TP, respectively. Agricultural fertilizer application and livestock were also important nutrient sources, which contributed 15% and 10% to TN, and 14% and 11% to TP, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Riverine discharge is indicated as the main nutrient source in Taihu watershed (Xu et al, 2010;Lai et al, 2006). Large amounts of untreated wastewater from factories and residential areas are discharged into Wangyu River through its polluted western side rivers (Hu et al, 2008(Hu et al, , 2010, bringing substantial exogenous nutrients into Ezhen, which could significantly impact the water quality into Lake Taihu and the efficiency of the water transfer project.…”
Section: Study Area and Field Samplingmentioning
confidence: 99%
“…Yan, Gao, and Huang () incorporated a water management scheme to model the irrigation and drainage operations of a polder in a lumped rainfall–run‐off model—the Wageningen Lowland Runoff Simulator. A number of studies have been conducted on the basis of distributed hydrological models in the plain river network regions once the distributed hydrological modelling techniques became widely used (Huang, Wang, Chen, & Huo, ; Lai & Yu, ; Lai, Yu, & Gui, ; Li et al, ; Luo, Su, Zhang, & Yang, ; Wang, ; Xu & Wang, ). These studies fall into three groups in terms of the way they address polders in watersheds.…”
Section: Introductionmentioning
confidence: 99%